2000
DOI: 10.1074/jbc.275.8.5318
|View full text |Cite
|
Sign up to set email alerts
|

The Acidic Triad Conserved in Type IA DNA Topoisomerases Is Required for Binding of Mg(II) and Subsequent Conformational Change

Abstract: The acidic residues Asp-111, Asp-113, and Glu-115 of Escherichia coli DNA topoisomerase I are located near the active site Tyr-319 and are conserved in type IA topoisomerase sequences with counterparts in type IIA DNA topoisomerases. Their exact functional roles in catalysis have not been clearly defined. Mutant enzymes with two or more of these residues converted to alanines were found to have >90% loss of activity in the relaxation assay with 6 mM Mg(II) present. Mg(II) concentrations (15-20 mM) inhibitory f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 22 publications
1
85
0
Order By: Relevance
“…Mg 2ϩ coordination with these residues is essential for enzyme function. The mutations in these acidic residues lead to impairment in the catalytic activity and cytotoxicity (38,39), indicating that targeting the topoI through these residues may impair the enzyme function. In our earlier studies, we showed that the mutations of the individual amino acids, D108 and E112, of the motif in MstopoI to alanine resulted in 20-and 5-fold losses of activity, respectively (38), while mutations of the acidic residues in MttopoI led to complete loss of activity (25).…”
Section: Resultsmentioning
confidence: 99%
“…Mg 2ϩ coordination with these residues is essential for enzyme function. The mutations in these acidic residues lead to impairment in the catalytic activity and cytotoxicity (38,39), indicating that targeting the topoI through these residues may impair the enzyme function. In our earlier studies, we showed that the mutations of the individual amino acids, D108 and E112, of the motif in MstopoI to alanine resulted in 20-and 5-fold losses of activity, respectively (38), while mutations of the acidic residues in MttopoI led to complete loss of activity (25).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, mutations at Glu-9 of E. coli topoisomerase I behaved somewhat differently. Replacement by alanine almost completely eliminated DNA cleavage, but glutamine supported high levels of DNA cleavage (although DNA relaxation activity was still severely compromised) (13,44,45). Moreover, replacement by alanine of Asp-111 (equivalent to Spo11p Asp-288) supported high levels of DNA cleavage and relaxation activity, whereas substitution at Asp-113 (equivalent to Asp-290 of Spo11p) caused a roughly 5-to 10-fold decrease in relaxation and a modest defect in DNA cleavage.…”
Section: Figmentioning
confidence: 99%
“…Two basic residues, Lys-13 and Arg-321 are required for the relaxation activities and have been proposed to interact with the DNA phosphates for DNA cleavage (16 -19). Three acidic residues Asp-111, Asp-113, and Glu-115 have been proposed to be responsible for coordinating two Mg 2ϩ ions (20). Asp-111 and Asp-113 are part of the TOPRIM motif DXDXXG conserved in nucleotidyl transferases for binding of divalent ions required for catalytic activity (21).…”
Section: From the Department Of Biochemistry And Molecular Biology Nmentioning
confidence: 99%